Cinnamide Derivatives of d‐Mannose as Inhibitors of the Bacterial Virulence Factor LecB from Pseudomonas aeruginosa - Sommer, Roman (John Wiley and Sons Inc., 2015)

(untitled) (ChemistryOpen)
Pseudomonas aeruginosa is an opportunistic Gram‐negative pathogen with high antibiotic resistance. Its lectin LecB was identified as a virulence factor and is relevant in bacterial adhesion and biofilm formation. Inhibition of LecB with carbohydrate‐based ligands results in a decrease in toxicity and biofilm formation. We recently discovered two classes of potent drug‐like glycomimetic inhibitors, that is, sulfonamides and cinnamides of d‐mannose. Here, we describe the chemical synthesis and biochemical evaluation of more than 20 derivatives with increased potency compared to the unsubstituted cinnamide. The structure–activity relationship (SAR) obtained and the extended biophysical characterization allowed the experimental determination of the binding mode of these cinnamides with LecB. The established surface binding mode now allows future rational structure‐based drug design. Importantly, all glycomimetics tested showed extended receptor residence times with half‐lives in the 5–20 min range, a prerequisite for therapeutic application. Thus, the glycomimetics described here provide an excellent basis for future development of anti‐infectives against this multidrug‐resistant pathogen.